Additional file 12 of Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark (13318734) (2025)
Additional file 12. Table S8—Single cell transcriptomic analyses following VHSV infection.